Answer: -4
Step-by-step explanation:
3-9=-6
-6*5=-30
-30-1=-31
6*-31=-186
-186+2=-184
8-2=6
6*7=42
42+4=46.
-184/46=-4
Answer:
b = 8
Step-by-step explanation:
Use the Pythagorean theorem
c^2 = a^2 + b^2
c = 10
a = 6
b = ?
Substitute into the formula
10^2 = 6^2 + b^2
100 = 36 + b^2 Subtract 36 from both sides
100 - 36 = b^2 Combine
64 = b^2 Take the square root of both sides.
√64 = √b^2
b = 8
<span>3.4 = –13.6 + (–3.4c) + 1.7c
</span><span>3.4 = –13.6 –3.4c + 1.7c
17 = -1.7c
c = -10</span>
Answer:
.50 cents
Step-by-step explanation: